Is targeting dysregulation in apoptosis splice variants in Mycobacterium tuberculosis (MTB) host interactions and splicing factors resulting in immune evasion by MTB strategies a possibility?. (September 2020) - Dlamini, Zodwa; Alaouna, Mohammed; Cholo, Moloko C.; Hull, Rodney
Abstract: Mycobacterium tuberculosis ( Mtb ), is one of the foremost organisms causing mortality in humans, and has been for most of human history. When faced with an infection the human immune system is ordinarily very competent in killing both extracellular and intracellular bacilli. However, Mtb is able to evade the host immune system and is even able to establish a persistent infectious reservoir by "hiding" in the immune cells of the host. While the mechanisms by which the bacteria accomplishes this are not fully understood, it is known that the bacterium can subvert cellular processes in cells such as macrophages that prevent the lysis of the bacteria or the cell undergoing apoptosis. They are also able to interfere with immune cell signalling. One of the greatest effects that Mtb has is too alter the transcriptome of the macrophage. An easy way for the bacterium to accomplish this is to alter the alternative splicing patterns of the host. This can lead to a large change in the population of different protein isoforms, some of which have very different functions when compared to the original protein. At the same time the long history of Mtb infecting humans have led to specific immune reactions that occur in the host immune system in order to fight the infection. Many of these specific reactions involve new isoforms of host defence proteins. In this way the human host can use alternate splicing to create new isoforms of immune- related proteins that are more effective in defending against Mtb .